2020
DOI: 10.1371/journal.pone.0230841
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic activity in the gluteus medius, gluteus maximus, biceps femoris, vastus lateralis, vastus medialis and rectus femoris during the Monopodal Squat, Forward Lunge and Lateral Step-Up exercises

Abstract: The Monopodal Squat, Forward Lunge and Lateral Step-Up exercises are commonly performed with one's own body weight for rehabilitation purposes. However, muscle activity evaluated using surface electromyography has never been analyzed among these three exercises. Therefore, the objectives of the present study were to evaluate the amplitude of the EMG activity of the gluteus medius, gluteus maximus, biceps femoris, vastus lateralis, vastus medialis and rectus femoris muscles in participants performing the Latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
7
26
1
Order By: Relevance
“…A previous study compared electromyographic activities (EMG) in the quadriceps during ECCs and CON cycling exercises, showing that the EMG amplitude during exercise was greater in the following order: vastus lateralis (17.3 ± 8.7%), vastus medialis (15.4 ± 4.4%), and rectus femoris (13.7 ± 7.3%; Penailillo et al, 2017a ). Although a different exercise mode was used, another study compared EMG amplitudes in the vastus lateralis, vastus medialis, and rectus femoris muscles during lateral step-up, forward lunge, and monopodial squat exercises, reporting that mean EMG during all exercises normalized to maximal voluntary isometric contraction in the vastus lateralis were significantly higher than those in the rectus femoris ( Muyor et al, 2020 ). The second bout of eccentric cycling (separated from the first bout by 2 weeks) in the vastus lateralis EMG amplitude was lower than the first bout, and muscle soreness developed only after the first bout ( Penailillo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study compared electromyographic activities (EMG) in the quadriceps during ECCs and CON cycling exercises, showing that the EMG amplitude during exercise was greater in the following order: vastus lateralis (17.3 ± 8.7%), vastus medialis (15.4 ± 4.4%), and rectus femoris (13.7 ± 7.3%; Penailillo et al, 2017a ). Although a different exercise mode was used, another study compared EMG amplitudes in the vastus lateralis, vastus medialis, and rectus femoris muscles during lateral step-up, forward lunge, and monopodial squat exercises, reporting that mean EMG during all exercises normalized to maximal voluntary isometric contraction in the vastus lateralis were significantly higher than those in the rectus femoris ( Muyor et al, 2020 ). The second bout of eccentric cycling (separated from the first bout by 2 weeks) in the vastus lateralis EMG amplitude was lower than the first bout, and muscle soreness developed only after the first bout ( Penailillo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al reported on EMG activities in mono-and biarticular muscles of the quadriceps femoris when hip and knee extension are combined; they showed that the EMG activities of the rectus femoris are inhibited and the vastus medialis is facilitated by combining hip extension with knee extension [22]. In addition, Mayer et al showed that the muscle activity of the vastus lateralis and vastus medialis was higher than that of the rectus femoris during squats; these reports support this result [23]. While squats involve the extension of the hip during the concentric phase, for which the hamstrings are a primary motor, it also involves the extension of the knee, to which the hamstrings are antagonists.…”
Section: Discussionmentioning
confidence: 91%
“…The maximum voluntary contraction (MVC) of each muscle was recorded during the 1RM test. Maximum peak muscle activation in microvolts (µV) at intervals of one second was calculated during the MVC for each muscle; this was used to normalize the sEMG [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%